Qualidade fisiológica de sementes de cultivares de soja em função do tratamento industrial de sementes durante armazenamento - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Recently, the use of industrial seed treatment (TIS) was introduced in Brazilian soybean plantations in order to treat seed lots during the beneficiation process. However, it is not yet known what the actual influence of the chemicals used in the mixtures used in TIS as insecticide, fungicide, nematicide, etc. is. on the physiological quality of soybean genotype seeds throughout storage. The objective of this work was to evaluate the effects of the treatment with chemical pesticides from the TIS on the physiological and sanitary quality of seeds of soybean cultivars during storage. A completely randomized design was used, in a 3 x 4 x 7 factorial scheme with subdivided plots in time, and four replications. The treatments were seed constituents from three soybean cultivars (M7110 IPRO; RR-8473RSF, M7739 IPRO), submitted to four chemical treatment combinations (fungicide / insecticide) applied via TIS: {T1-control; T2-fungicide (Derosal Plus® - 200 mL); T3-insecticide (Cruiser ® - 500 mL); (0, 30, 60, 90, 120, 150, and 180 days) were stored for six months. The seeds were stored in a cold room regulated at 12 ± 2 ºC and relative humidity of ± 45%. The following analyzes were carried out: water content, germination, first count, radicle and hypocotyl length, dry shoot and root mass, and accelerated aging. The data were submitted to analysis of variance initially, and later discriminated by the Scott-Knott test (p <0.05) (cultivars and chemical products) and regression (storage period). It is concluded that the cultivar M-7110 IPRO was superior to the others in the tests of seed quality and vigor during the entire period of storage. The use of insecticide favored the length of seedlings in cultivar RR-8473 RSF. Chemicals affected seed quality and vigor in all studied cultivars. Soybean seeds can be kept stored with chemical treatment for commercial purposes up to 60 days.
Keywords: Glycine max L. Merrill; Cultivares; Qualidade de sementes; TIS; Glycine max L.; Quality; Cultivars; TIS; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA